Demographic Transition and Changing Age Structure in Nepal - Sharma, Tilak Prasad; Shakya, Dhanendra Veer (Tribhuvan University Journal, 2025)
This paper focuses on the demographic transition of Nepal and the changing age structure between 1952/1954 and 2021. It is a quantitative study and has adopted descriptive and analytical methods to secondary data, which was collected during the 2021 Census with emphasis on general age groups, dependency ratios, and working-age population growth rates. The findings indicate that the decrease in the pre-working age population, from over 40 percent in the initial years of the census 1952/54 to 27.8 percent in the year 2021 was significant with the rise of the working-age population from 54.1 percent to 65.2 percent, which indicates that Nepal has entered into the demographic dividend phase. The population aged above 65 (after working age) grew by 2.9 to 6.9 percent, with early signs of population aging. The highest dependency ratios of 84.8 were recorded in 1991 but declined to 53.3 in 2021, which demonstrates that there is a large number of people of working age. At the same time, growth rates of working-age population continue to beat aggregate population growth consistently, and this suggests that there is a possibility of higher economic production. The results suggest that Nepal is experiencing a structural change that will provide an opportunity to economic growth, as long as workforce markets, education, and human capital investments are correlated with demographic realities. Nonetheless, the increasing number of the elderly accentuates the significance of timely planning in the social protection system, healthcare, and long-term care systems. This paper highlights the need to have policies that can maximize the demographic dividend as well as provide solutions to the emerging aging-related challenges, thus providing socioeconomic growth in the long term.